PEMENUHAN ASUPAN GIZI ANAK MELALUI BEKAL MAKANAN SEHAT BAGI KESEHATAN ANAK USIA DINI - Aulia Insani (Journal of Innovation Research and Knowledge, 2022)
The developments experienced by early childhood from childhood to a adulthood form a good personality with a healthy physique. Factors that affect the growth of childrren do not escape the intake of nutrients or healthy food given by parents to their children with great affection. In recent years, there may be a lot of news circulating about the decline in nutritional intake that develops in children which is influenced by several factors including parents. Actually, children’s nutritional intake can not only be given at home when they are with their parents, but it can be done by bringing healthy food supplies for then to take to school and eat together. Of course, with nutritional intake and using menu they like so that they are interested in consuming these foods, their nutritional intake will continue to be monitored.